Evaluating Nutritional Standards and Fiscal Sustainability in Free School Meal Programs - Naufal Faryreza Ryanta; Salsabila Najwa Asri; Jita Gabela; Salsabila Ramadhani; Putri Yanti (Genius Journal, 2026)
Introduction: Childhood obesity is a global health emergency that threatens the quality of Indonesia's human resources. Indonesian Health Survey (IHS) recorded an increase in adult obesity prevalence from 23.4% to 21.8% in 2018. National indicators estimate that approximately 18.8% of children aged 5-12 years are overweight and 10.8% are obese. Objective: This study aims to evaluate the impact of Ultra-Processed Foods (UPF) on the Makan Bergizi Gratis (MBG) program through an integration of public health, nursing, Islamic psychology, and accounting perspectives. Method: The method used was a narrative literature review with an electronic literature search in Google Scholar, PubMed, SINTA, and ScienceDirect databases for the 2019–2026 period. Result: The results show that UPF triggers biological sabotage through insulin resistance and disruption of the leptin-ghrelin hormone. Psychoneurobiologically, the hyperpalatable nature of UPF hijacks the brain's reward system, triggering food addiction. Implementation analysis revealed a fatal food safety gap that resulted in 5,620 student food poisoning and a crisis of public trust due to low dietetic standards in the field. From an accounting perspective, the use of UPF constitutes a "pseudo-efficiency" that creates contingent liabilities in the form of inflated future health costs. Conclusion: The study's conclusion emphasizes that the success of MBG should be measured by the integration of nutritional audits and the use of fresh local ingredients to break dependence on industrial food and ensure sustainable investment in human resources.